Biobased Thermoset Sandwiched Composites Enabled by Dynamic Covalent Chemistry for Electrical Insulation, EMI Shielding, and Thermal Management - Xiao‐Li Zhao; Ling‐Yu Li; Yi‐Dong Li; Jian‐Bing Zeng (SusMat)
ABSTRACT Sandwiched composites with a combination of electromagnetic interference (EMI) shielding performance, thermal conductivity, and electrical insulation show significant potential in electronic packaging. However, the fabrication of such composites using high‐performance thermosets as matrices presents challenges due to their permanently crosslinked structures. Here, we relied on the dynamic covalent chemistry to propose an innovative interface‐welding strategy to fabricate a sandwiched thermoset (covalent adaptable network)/carbon nanotubes/boron nitride (CAN/CNTs/BN) composite. To sustainability, the CAN matrix was derived from renewable biobased resources, such as vanillin, glycerol triglycidyl ether, and 1,10‐diaminodecane. The incorporation of CAN/BN composites as the outer layers bolstered thermal conductivity while maintaining electrical insulation, while the CAN/CNTs interlayer efficiently attenuated electromagnetic waves. With a BN and CNT content of 30 wt%, the CAN/CNTs/BN composite achieved a thermal conductivity of 1.79 W·m−1·K−1, an EMI shielding effectiveness exceeding 55 dB in the X‐band, and an ultra‐low electrical conductivity of 1.6×10−13 S·m−1. Leveraging dynamic covalent chemistry, the interface‐welding technique fostered fully integrated interfaces, ensuring superior mechanical properties of CAN/CNTs/BN composite including a tensile modulus of 3837.8 ± 196.9 MPa and tensile strength of 62.1 ± 3.7 MPa. Additionally, its exceptional heat dissipation performance positions CAN/CNTs/BN composite as a promising contender for electronic packaging applications.